Plant biotechnology and genetics : principles, techniques, and applications - Stewart, C. Neal
"This book can be used in a junior or senior level course, including masters students in plant biotechnology or plant genetics, as well as in special topics classes for both undergraduate and graduate students"--Provided by publisher.